Congenital cystic eye with multiple dermal appendages: a case report - Gupta, Pankaj (BioMed Central, 2003)
BACKGROUND: A partial or complete failure in the involution of the primary optic vesicle resulting in the formation of a cyst is an extremely rare anomaly known as congenital cystic eye. The primary optic vesicle is formed but instead of the anterior part of the vesicle involuting to lie in apposition with the posterior part, a cyst persists at birth and replaces the eye. CASE PRESENTATION: We report a case of congenital cystic eye associated with multiple dermal appendages in a 1-day-old female child. This condition presented at birth as a large orbital mass in the left orbit that bulged forwards and stretched the eyelids. No globe or any other ocular structures were identified in the orbit. Multiple dermal appendages were present in the adjacent part of the face below the left orbit and on the upper part of the neck. CONCLUSIONS: Congenital cystic eye is an extremely rare condition and with only 28 previous cases reported in the literature. We present the second case of congenital cystic eye with multiple dermal appendages of the face and neck.